Natural products as novel reagents for the detection of latent fingermarks - Jelly, Renee Michelle (Curtin University, 2010)
The ability to detect latent fingermarks on porous surfaces, such as paper-based documents, is extremely important in resolving criminal cases. Detection methods that target amino acids present in latent fingermark deposits have achieved widespread use. This is due to the chemical stability of this component of the eccrine secretion and the binding of the amino acids to paper fibres, thus resulting in a good representation of the fingermark. This dissertation presents studies into the ability of naphthoquinones to develop latent fingermarks on paper surfaces. These compounds represent a completely new class of fingermark detection reagents.Lawsone (2-hydroxy-1,4-naphthoquinone), the compound thought to be responsible for the staining properties of henna, was found to react with latent fingermarks on porous surfaces to yield purple/brown images that exhibit photoluminescence without further treatment. Luminescence spectrophotometry of developed amino acid spots on paper indicated that lawsone is reacting with the amino acids in latent fingermarks. A mechanism for this reaction is postulated.Lawsone is a naphthoquinone, a group of compounds, which are known for reacting with amino acids to produce highly coloured compounds. On this basis, the following naphthoquinones were selected for subsequent investigations: 1,4-dihydroxy-2-naphthoic acid; 1,2-naphthoquinone-4-sulfonate; 2-methoxy-1,4-naphthoquinone; and 2-methyl-1,4-naphthoquinone. All of the tested compounds yielded brown visible impressions, which also exhibited luminescence. Luminescence spectrophotometry revealed differences in photoluminescence characteristics for fingermarks developed with the different naphthoquinones with excitation over the range 530-590 nm. Luminescence spectrophotometry of developed amino acid spots on paper confirmed that the naphthoquinones were reacting with amino acids in the latent fingermarks.Fingermarks and amino acids on cellulose thin layer chromatography plates were developed with lawsone and the additional selected naphthoquinones listed above. These specimens were then subjected to analysis by synchrotron infrared microscopy. Despite significant issues with the presence of a cellulose background signal, it was possible to successfully obtain spectra of the reaction products in-situ. In an attempt to rationalise these results, lawsone was reacted with glycine in solution to afford a mixture of two coloured compounds. These compounds were characterised and one was tentatively identified as 2-amino-1,4-naphthoquinone or a structural isomer thereof. A structure could not be assigned to the second compound, however nuclear magnetic resonance spectroscopy indicated a symmetrical dimer, containing two lawsone moieties.Some preliminary results are presented for a screening of additional natural product based colour forming compounds as latent fingermark detection reagents. Two compounds, juglone and alizarin, were found to successfully develop latent fingermarks on paper. In addition a systematic retrosynthetic approach was taken to explore the potential of a natural dye precursor as a fingermark reagent. Finally, a serendipitous discovery of the skin dyeing properties of 6-N,N-dimethylaminofulvene, provided an additional route to a possible class of fingermark detection compounds unrelated to ninhydrin. These preliminary studies indicate potential strategies for further research towards novel latent fingermark reagents for porous surfaces.